2011
DOI: 10.1111/j.1600-0501.2011.02319.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implant placement in molar regions: a 12‐month prospective, randomized follow‐up study

Abstract: After 12 months of loading, no significant differences in peri-implant bone level were observed after the use of three bone regenerative techniques in connection with immediately placed implants in molar regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Survival was defined as implants remaining in situ at the follow-up examinations, irrespective of their conditions. All 20 studies reported survival rates, leading to a weighted mean survival rate of 96.6% with 95% CI (93.5-99.7) [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Certain considerations must be taken into account when interpreting the estimates of the individual studies: the study by Atieh et al shows a greater standard deviation, due to the small sample size, only 12 implants [13].…”
Section: Implant Survivalmentioning
confidence: 99%
See 3 more Smart Citations
“…Survival was defined as implants remaining in situ at the follow-up examinations, irrespective of their conditions. All 20 studies reported survival rates, leading to a weighted mean survival rate of 96.6% with 95% CI (93.5-99.7) [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Certain considerations must be taken into account when interpreting the estimates of the individual studies: the study by Atieh et al shows a greater standard deviation, due to the small sample size, only 12 implants [13].…”
Section: Implant Survivalmentioning
confidence: 99%
“…The studies included in this systematic review that analyzed survival and success rates as well as MBL depending on the type of implant-abutment connection [13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] reported no statistically significant for implant survival rate (p = 0.511) success rate (p = 0.463) and MBL (p = 0.393) around implants with internal or external connections.…”
Section: Type Of Implant-abutment Connectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with the present findings, Liñares et al, 21 in a similar model that lacked augmentation procedures, found a relatively high degree of bone loss around immediate implants, ranging from 2.5 to 2.6 mm from implant shoulder to bone crest and 3.2 to 2.8 mm from implant shoulder to first BIC. On the contrary, radiographic bone loss of a much lesser extent (1.1 mm on average) was reported by Urban et al, 22,23 who compared different augmentation techniques in conjunction with immediate implantations in molar extraction sites.…”
Section: Discussionmentioning
confidence: 84%